Cross-sectoral coordination in the implementation of agroforestry in Malawi - Nicholas P. Ndlovu (Frontiers in Forests and Global Change)
IntroductionAgroforestry’s integration into policies and strategic frameworks is increasing globally, reflecting its critical role in sustainable land-use management. However, realizing the full potential of these policies depends on effective implementation, which necessitates coordination among actors with overlapping responsibilities and siloed approaches. Despite its importance, research on coordination during agroforestry implementation is limited. This study aims to fill this gap by examining coordination in Malawi, particularly among actors from different sectors.MethodsThe study utilizes a qualitative approach based on coordination theories to examine the implementation of agroforestry activities in Malawi. Data was collected through semi-structured interviews with high-level actors involved in agroforestry. Thematic analysis identified key factors influencing coordination.ResultsThe results indicates that several key factors, which include clear institutional arrangements, trust adequate resources, and political supportive as crucial in facilitating cross-sectoral collaboration. Weak institutional frameworks and fragmented governance hinder coordination efforts.DiscussionThe findings suggest that coordination is vital for the successful implementation of agroforestry. However, relying on social capital and historical relationships to form partnerships limits broader participation and reduces the diversity of perspectives in agroforestry. Furthermore, coordination supports the survival of various actors by allowing them to pool resources, share risks, and access knowledge and markets that would be challenging to secure independently.ConclusionIn conclusion, the success of agroforestry success depends not only on well-defined policies, but effective implementation, and robust coordination among diverse stakeholders. Closing policy gaps and building trust-based partnerships are crucial for unlocking its full benefits. Through understanding and optimizing different factors, policy implementors can develop more inclusive, well-resourced, and context-aware coordination strategies.